Psychological and Social Impact of Recurrent Aphthous Ulcers among Young Adults - Pathak, Swarnasmita; Jyoti, Bhuvan; Simlai, Jayati (International Research Journal of Ayurveda & Yoga, 2026)
Chronic kidney disease (CKD) is a progressive and irreversible renal disorder associated with systemic complications and reduced quality of life. In Ayurveda, CKD can be correlated with Vṛikka Vikāra, arising due to imbalance of Tridoṣha (primarily Vāta and Kapha) leading to impaired Mutravaha Srotas function. Ayurvedic management focuses on Śodhana (detoxification) and Śamana (pacification) therapies along with ayurvedic formulations to improve renal function and alleviate symptoms. This holistic approach aims to enhance quality of life and slow disease progression. A 44-year-old male with a known case of CKD presented to Jeena Sikho Lifecare Limited Hospital, Lucknow, with complaints of fever (Jvara), generalized weakness (Daurbalya), gastric disturbances (Amlapitta), headache (Śiraśhūla), vomiting (Chhardi), throat infection (Kaṇṭhaśotha), shortness of breath (Śvāsa), disturbed sleep (Nidrānāśha), and generalized body ache (Aṅgamarda). The patient was managed with a comprehensive Ayurvedic treatment protocol including Ahāra–Vihāra Chikitsā (dietary and lifestyle modifications) and Panchkarma therapies. Following the intervention, complete resolution of fever, headache, vomiting, and generalized weakness was observed, with marked improvement in dyspnea, sleep quality, and body pain. Laboratory investigations showed a reduction in blood urea from 78.23 mg/dl to 68.8 mg/dl and improvement in glomerular filtration rate (GFR) from 12.11 ml/min to 24.08 ml/min. However, serum creatinine slightly increased from 3.22 mg/dl to 3.60 mg/dl, indicating persistent chronic renal impairment. Ayurvedic and Pañchkarma-based interventions demonstrated significant symptomatic relief and supportive improvement in renal function parameters in this CKD patient. These findings suggest that Ayurveda may serve as an adjunctive therapy in CKD management further controlled clinical studies are required to validate its efficacy.